2012
DOI: 10.1074/mcp.m111.009449
|View full text |Cite
|
Sign up to set email alerts
|

Profilin 1 is a Potential Biomarker for Bladder Cancer Aggressiveness

Abstract: Of the most important clinical needs for bladder cancer (BC) management is the identification of biomarkers for disease aggressiveness. Urine is a "gold mine" for biomarker discovery, nevertheless, with multiple proteins being in low amounts, urine proteomics becomes challenging. In the present study we applied a fractionation strategy of urinary proteins based on the use of immobilized metal affinity chromatography for the discovery of biomarkers for aggressive BC. Urine samples from patients with non invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 62 publications
6
97
0
1
Order By: Relevance
“…Its expression is decreased in multiple types of carcinoma (breast, bladder, and pancreas) (10 -14), and its ectopic re-expression inhibits the proliferation and survival of several cancer cell lines in vitro and in vivo (12, 14 -16). Recently, low Pfn1 expression was correlated with poor outcome of bladder and pancreatic cancer patients (13,14). However, unlike classic tumor suppressor genes, homozygous deletion and somatic mutations of the PFN1 gene are extremely rare and have not been causally linked to cancer.…”
Section: Pfn1mentioning
confidence: 99%
“…Its expression is decreased in multiple types of carcinoma (breast, bladder, and pancreas) (10 -14), and its ectopic re-expression inhibits the proliferation and survival of several cancer cell lines in vitro and in vivo (12, 14 -16). Recently, low Pfn1 expression was correlated with poor outcome of bladder and pancreatic cancer patients (13,14). However, unlike classic tumor suppressor genes, homozygous deletion and somatic mutations of the PFN1 gene are extremely rare and have not been causally linked to cancer.…”
Section: Pfn1mentioning
confidence: 99%
“…[59][60][61][62] We surprisingly found that breast cancer cells and even normal human mammary epithelial cells (HMEC) display hypermotile phenotype when Pfn1 expression is suppressed, and conversely, overexpression of Pfn1 suppresses breast cancer cell motility. 25,63 Similar apparent inverse correlation between Pfn1 expression and tumor cell motility has also been documented for hepatocarcinoma cells.…”
Section: Context-specific Effect Of Pfn1 In Cell Motilitymentioning
confidence: 99%
“…3,[5][6][7] By contrast, pfn1 decreases motility and invasiveness of breast cancer cells in a mouse model 8 and is down-regulated in invasive bladder cancer cells compared with noninvasive counterparts. 9 The in vivo role of pfn1 in tissue-specific stem cells has not been reported. The availability of the pfn1 flox/flox mice provided us an opportunity to clarify the function of pfn1 in different tissues and stem cells in the whole animal.…”
Section: Introductionmentioning
confidence: 99%